Analysis of Factors Driving Displacement Private Vehicle User Mode to KRL Green Line (Cisauk-Tanah Abang) - Diah Savitri; Ocky Soelistyo Pribadi; Aswanti Setyawati (Dinasti Publisher, 2024)
This study analyzes the factors encouraging private vehicle users to switch to the KRL Line. With population growth and transportation needs in the Cisauk Sub-district, it is necessary to understand that many commuter users still choose private vehicles, even though KRL offers advantages such as low-cost efficiency in time. This research uses a qualitative approach with group and discussion methods to identify factors influencing decisions. The data was analyzed using a qualitative descriptive approach with the Nvivo 12 application. The results showed that convenience, stations, and parking facilities influence mode switching. This research is expected to provide recommendations to KRL operators and policymakers to improve service quality and support facilities so that more private vehicle users switch to public transportation. In addition, this study provides practical advice for developing public transportation in other areas with similar characteristics.